2015
DOI: 10.1093/bioinformatics/btv662
|View full text |Cite
|
Sign up to set email alerts
|

rHAT: fast alignment of noisy long reads with regional hashing

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…If B gets more votes, then it is more likely to be clone code of A. The idea is similar to the idea of seed-and-extend in the sequencing alignment [8]. The threshold for SR A (B) is θ (line 17).…”
Section: Filtering Via the Common Seeds Numbermentioning
confidence: 99%
“…If B gets more votes, then it is more likely to be clone code of A. The idea is similar to the idea of seed-and-extend in the sequencing alignment [8]. The threshold for SR A (B) is θ (line 17).…”
Section: Filtering Via the Common Seeds Numbermentioning
confidence: 99%
“…conLSH [8] . The aligner, rHAT [20] has been excluded from the study, as it has been reported to malfunction in certain scenarios [17]. The PacBio read alignment module of BWA-MEM [15]…”
Section: Mapper Command Line Settingsmentioning
confidence: 99%
“…However, the high sequencing error rate of 13-15% per base [2] poses a real challenge in sequence analysis. Specialized methods like BWA-MEM [15], BLASR [6], rHAT [20], Minimap2 [17], lordFAST [9], etc., have been designed to align noisy long reads back to the respective reference genomes. BLASR [6] clusters the matched words from the reads and genome after indexing using suffix arrays or BWT-FM [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chou's5 -step rule [17] and demonstrated in as eries of recent publications, [18][19][20][21][22][23][24][25][26] to presentas tatistical predictorf or ab iological system with ac lear logic and application value, we need to consider the following guidelines: ( 1) how to construct or select av alid benchmark dataset to train and test the predictor; (2) how to formulate the biological sequence samples with an effective mathematical expression thatc an truly reflect their intrinsic correlation with the targett ob ep redicted; (3)h ow to introduce or develop ap owerful algorithm (or engine) to operate the prediction;( 4) how to properly perform cross-validation tests to objectively evaluatei ts anticipated accuracy; ( 5) how to establish au ser-friendlyw eb-server that is accessible to the public. Below, let us describet he five procedures one-by-one.…”
mentioning
confidence: 99%